Information Needs of Fish-Feed Entrepreneurs in Kainji Lake Basin Nigeria - Godfrey Onyekachukwu Nwabeze; Bamidele A Ibeun; Sunday Faleke; Eunice N Belonwu; Chris A Igene; Kalu I Ogbonna; Victor A Nwanjoku; Alex Ighoro (Journal of Agricultural Extension, 2017)
This study examined information needs of fish-feed entrepreneurs in the Kainji Lake Basin, Nigeria. The objectives of the study are to examine the socio-economic characteristics of the respondents, identify extension needs of the respondents, determine the profitability of fish feed production and identify challenges in fish feed enterprise. Multistage sampling technique was used to select twenty-nine respondents for the study. Semi-structured interview schedule was employed for data collection. Data were analysed using percentages, mean, standard deviation and cost analyses function. The study revealed that 41.4% of the respondents were within the age bracket 40-44 years with mean age of 41 years. Majority (93.1%) of the respondents were married with 48.2% of the respondents having educational qualification beyond secondary level.  The challenges of operating fish feed enterprise in the area were high cost of fish meal (mean=3.76, SD= 0.51), lack of access to credit (mean=3.48, SD= 0.74) and lofty cost of operating milling machine (mean=2.93, SD= 3.70).  The profitability analysis for investing in fish feed enterprise revealed that the gross margin per unit fish feed was â‚¦49.85. The respondents require information from extension on access to credit facility and training on cost effective fish feed formulation.  Therefore linkage with credit sources and training skill on fish feed formulation should be incorporated into fisheries training to ensure effective extension delivery system.